Teachers’ Understanding of the Multi-Dimensions of Communicative Language Teaching: A Case Study of Thai Universities - Saengboon, Saksit (Kasetsart Journal of Social Sciences, 2014)
This study explored teachers’ understanding of the multi-dimensions of communicative language teaching (CLT). A questionnaire was administered to 135 Thai EFL university lecturers; 83 completed questionnaires were returned. Semi-structured interviews were conducted with three participants and one Thai expert in English as a foreign language. The findings revealed that the participants appeared to have a good understanding of CLT principles, although several construed the CLT ideology of choice and freedom as far-fetched. Although the participants realized that CLT is the way forward, strict adherence to CLT should be avoided. Moreover, cautious optimism is much needed, for local teaching and learning conditions must be considered. Finally, implications for further research revolving around CLT were provided—namely, an ethnographic study of CLT, students’ beliefs about the efficacy of CLT and critical discourse analysis concerning CLT.